Evaluation of high-throughput methodology for multi-gene screening in patients with Non-Alcoholic Fatty Liver Disease (NAFLD) - Fisher, Leslie Reginald (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScMedSc)--Stellenbosch University, 2011.